Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
Step-by-step explanation:
7) a - 4b -c = -20 -------------(I)
3c = -6 ------------------(II)
2a +5c = -22 ---------------(III)
3c = -6 {Divide both sides by 3}
c = -6/3
c = -2
Plugin c = -2 in equation (III)
2a + 5c = -22
2a + 5*(-2) = -22
2a - 10 = -22
2a = -22 + 10
2a = -12
a = -12/2
a = -6
Plugin a = -6 and c = -2 in equation (I)
a - 4b -c = -20
-6 - 4b -(-2) = -20
-6 - 4b + 2 = -20
-4b - 4 = -20
-4b = -20 + 4
-4b = -16
b = -16/4
b= -4
8) b = 2a - 9 -----------(I)
3a - 3c = 21 -------------(II)
c = a -5b- 22
-a + 5b + c = -22 -----------(III)
Multiply equation (III) by 3 and then add to equation(II)
(III)*3 -3a + 15b + 3c = -66
(II) 3a + 0b - 3c = 21 {Now add}
15b = -45 {Divide both sides by 15}
b = -45/15
b = -3
Plugin b = -3 in equation (I)
b = 2a - 9
-3 = 2a - 9 {Add 9 to both sides}
-3 +9 = 2a
2a = 6 {Divide both sides by 2}
a = 6/2
a = 3
Plugin a = 3 in equation(II)
3a - 3c = 21
3*3 - 3c = 21
9 - 3c = 21 {subtract 9 from both sides}
-3c = 21 - 9
-3c = 12 {Divide both sides by 2}
c = 12/-3
c = -4
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.